Profile Characteristics of Agri Input Dealers in Telangana State: Researchable Areas for Stakeholders - Rajitha, B.; S. Sontakki, Bharat; Mohan Reddy, M. Jagan; Sagar, G.E.CH Vidya (Journal of Agricultural Extension Management, 2022)
Agricultural extension helps in transfer of technology, adoption of innovations, increasing efficiency in agriculture production. Public extension service providers included SDA, DAATTC, KVK, ATMA etc. As these are ineffective to reach every corner of the country, private extension service providers entered the scenario. Private extension service providers included-Input agencies, large Agri business firms, farmer organizations and producer cooperatives, NGOs, etc. According to the NSSO data (2005), Agri. Input Dealers (AIDs) are the primary source of farm information to the farmers. Percentage of farmer households accessing farm information through KVKs-0.7%, extension worker-5.7%, Agri. Input Dealers -13.1%. This paper focused to study the profile characteristics of Agri. Input Dealers. Ex-post facto research design was adopted for the study with a sample of 90 respondents covering 3 districts of Telangana. From the analysis, it was found that majority of respondents fall under medium profile characteristics